The incidence and risk factors of sepsis following ovarian cancer surgery: A retrospective Nationwide Inpatient Sample database study - Yu Wang; Jing Zheng; Qun Lv; Guang-Min Xu; Hao Xie; Bo-Fei Dong; Xue Wang (PLoS ONE, 2026)
Background Postoperative sepsis is a significant complication following ovarian cancer surgery. However, limited studies have explored the risk factors associated with postoperative sepsis following ovarian cancer surgery in this context. This study aimed to assess the prevalence of postoperative sepsis and identify its associated risk factors. Methods This study retrospectively analyzed data from patients who underwent ovarian cancer surgery between January 2010 and December 2019 using the Nationwide Inpatient Sample (NIS) database. The age range of the study population is between 18 and 99 years old. Patients were categorized into two groups based on the presence or absence of postoperative sepsis. Data on patient demographics (e.g., race, age), hospital characteristics (e.g., insurance type, bed size, teaching status, region), preoperative comorbidities, and postoperative complications were extracted for comparison. Univariate and multivariable logistic regression analysis were conducted to identify factors associated with postoperative sepsis. Results A total of 39,049 patients were identified in the NIS database. Among them, 1,288 cases of postoperative sepsis were observed, representing an incidence rate of 3.3%. Patients with postoperative sepsis exhibited higher hospital charges, advanced age, prolonged length of stay (LOS), and increased in-hospital mortality. Preoperative risk factors for postoperative sepsis included congestive heart failure, coagulopathy, metastatic cancer, etc. Postoperative sepsis was associated with major complications, including electrolyte imbalance, urinary tract infection, thrombocytopenia, etc. Conclusions The incidence of postoperative sepsis following ovarian cancer surgery has shown a slight increase over time. Postoperative sepsis is associated with advanced age, race, prolonged LOS, higher hospital charges, in-hospital mortality, preoperative comorbidities, and perioperative complications. Recognizing these risk factors is essential for improving patient prognosis.